A Network Meta-analysis Comparing Exenatide Once Weekly with Other GLP-1 Receptor Agonists for the Treatment of Type 2 Diabetes Mellitus. Issue 1 (March 2016) - Kayaniyil, Sheena; Lozano-Ortega, Greta; Bennett, Heather; Johnsson, Kristina; Shaunik, Alka; Grandy, Susan; Kartman, Bernt
Abstract Introduction Exenatide is a glucagon-like peptide-1 receptor agonist (GLP-1 RA), approved for treatment of type 2 diabetes mellitus (T2DM). There is limited direct evidence comparing the efficacy and tolerability of exenatide 2 mg once weekly (QW) to other GLP-1 RAs. A network meta-analysis (NMA) was conducted to estimate the relative efficacy and tolerability of exenatide QW versus other GLP-1 RAs for the treatment of adults with T2DM inadequately controlled on metformin monotherapy. Methods A systematic literature review was conducted to identify randomized controlled trials (RCTs) that investigated GLP-1 RAs (albiglutide, dulaglutide, exenatide, liraglutide, and lixisenatide) at approved doses in the United States/Europe, added on to metformin only and of 24 ± 6 weeks treatment duration. A Bayesian NMA was conducted. Results Fourteen RCTs were included in the NMA. Exenatide QW obtained a statistically significant reduction in glycated hemoglobin (HbA1c) relative to lixisenatide 20 µg once daily. No other comparisons of exenatide QW to other GLP-1 RAs were statistically significant for change in HbA1c. No statistically significant differences in change in weight, systolic blood pressure, risk of nausea or discontinuation due to adverse events were observed for exenatide QW versus other GLP-1 RAs. Conclusion Exenatide QW demonstrated similar effectiveness and tolerability compared to other GLP-1 RAs, for the treatment of T2DM in adults inadequately controlled on metformin alone.